2001
DOI: 10.1523/jneurosci.21-02-00527.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mode and Tempo of Tangential Cell Migration in the Cerebellar External Granular Layer

Abstract: After their final mitosis, cerebellar granule cells remain in the external granular layer (EGL) for 20-48 hr before initiating their radial migration across the molecular layer (ML), but the significance of this latent period is not well understood. In the present study, we used a confocal microscope to examine morphogenetic changes and behavior of postmitotic granule cells restricted to the EGL in slice preparations of the postnatal mouse cerebellum. We found that, coincident with the extension of two uneven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
177
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 54 publications
8
177
0
5
Order By: Relevance
“…In previous in vitro studies, the intermittent stops during the migration of individual cells were rather brief, giving an impression of a continuous movement [11,15,34,35], but many JGNs analyzed here stopped for very long time periods (from 12 h to a few days) before resuming the movement. Continuous imaging of the cells at high temporal resolution, i.e., every 15 min, revealed that cells were migrating at median speeds of 0.4-0.8 µm/min, or 24-48 µm/h, which are comparable to the values obtained in organotypic slices from perinatal mice for cells detaching from the RMS and starting radial migration into the bulb [12], or for SVZ neuroblasts migrating in exploratory/intermediate manner in acute OB slices from juvenile/adult mice [15].…”
Section: Discussionmentioning
confidence: 74%
“…In previous in vitro studies, the intermittent stops during the migration of individual cells were rather brief, giving an impression of a continuous movement [11,15,34,35], but many JGNs analyzed here stopped for very long time periods (from 12 h to a few days) before resuming the movement. Continuous imaging of the cells at high temporal resolution, i.e., every 15 min, revealed that cells were migrating at median speeds of 0.4-0.8 µm/min, or 24-48 µm/h, which are comparable to the values obtained in organotypic slices from perinatal mice for cells detaching from the RMS and starting radial migration into the bulb [12], or for SVZ neuroblasts migrating in exploratory/intermediate manner in acute OB slices from juvenile/adult mice [15].…”
Section: Discussionmentioning
confidence: 74%
“…It may be that radial and tangential migration modes are not specific to neurons releasing a specific neurotransmitter. Indeed, in the cerebellum, inhibitory principal Purkinje neurons exhibit radial migration, whereas excitatory modulatory granule neurons migrate tangentially as well as radially (23). A very small number of glutamatergic modulatory interneurons are also generated in the adult SVZ and migrate tangentially to the olfactory bulb (24).…”
Section: Discussionmentioning
confidence: 99%
“…In other neuronal subpopulations undergoing long-range migration, neuronal morphogenesis undergoes extensive stereotypical changes, leading to polarized outgrowth of their axon and dendrites. This is the case for cerebellar granule neurons (CGN) as well as cortical and hippocampal pyramidal neurons (PN), two of the best-studied models of neuronal polarization (Rakic 1971;Rakic 1972;Shoukimas and Hinds 1978;Gao and Hatten 1993;Komuro et al 2001;Hatanaka and Murakami 2002;Noctor et al 2004). Both CGN and PN acquire their axon -dendrite polarity from the polarized emergence during migration of their trailing and leading processes, respectively (Fig.…”
Section: Axon Initiation In Vivomentioning
confidence: 99%